Digital Payment Systems (Qris) And Financial Transaction Efficiency: A Qualitative Review Of Implementation Practices - Agus Rohmat Hidayat (PT. Publikasiku Academic Solution, 2026)
System digital payments in Indonesia are growing fast, one of them through QRIS (Quick Response Code Indonesian Standard), which is designed For make things easier transaction finance, improve digital inclusion, and accelerate efficiency MSME operations and institution finance. However, the effectiveness QRIS implementation in practice real and its impact to efficiency transaction Still need understanding deep. Study This aim For explore practice QRIS implementation in various sector and assess its influence to efficiency transaction finance, using approach qualitative based studies literature and analysis document. Study This use approach qualitative with review literature systematic, interview with MSMEs, banks, and fintech players, as well as observation practice transaction QRIS- based. Data analyzed in a way thematic For extracting pattern use, obstacles, and benefits of QRIS for efficiency transactions. Research results show that QRIS improves efficiency transactions, speed up the payment process, reduce cost administration, and improve accuracy recording. Challenges encountered covering digital literacy, limitations internet network, and resistance users beginning. The use of QRIS is also encouraging transparency finance and integration with system digital banking. Research This give guide for banks, fintech, and MSMEs in maximize utilization of QRIS, as well as give recommendation policy For expand use system digital payments to increase efficiency transactions and inclusion finance.